A Need Analysis Distance Learning Syllabus Development Based on Cooperative Learning Method for Speaking Skill - Desy Sanabila (STKIP AGAMA HINDU SINGARAJA, 2022)
Distance learning syllabus development needed to adapt to the current distance learning conditions. The aim of this research was to analyze the syllabus that was applied in the classroom and helped the students to fulfill their needs. In this study, an analysis was conducted to get the students’ responses to the syllabus that had been used during online learning activities. The subject of the research was the students of 10th grade in SMA Negeri 1 Sampang. The sample was chosen randomly from as many as 10 students. This research was conducted using a qualitative method as a design to collect the data. The instrument of this research was used questionnaire distributed using Google Form. The result of the study was shown in descriptive qualitative. As the result, the research was found that speaking learning skill was important to conduct by applied cooperative learning and it was important for the teacher to have the observation to develop the distance learning syllabus.